Design and optimization of data center performance - Tang, Rongjun. (2013)
Disk storage technologies have not advanced since the last major introduction of the network storage architecture, mainly in the Storage Area Networks (SAN) and Network Attached Storage (NAS). Hence, it is the main cause of bottlenecks in systems today. Conversely, processing power technologies and network technologies have made significant progress to increase their performance. The hybrid storage system is currently widely adopted for data caching, where frequently accessed files will be moved into the SSD to obtain faster I/O, hence contributing to a decrease in overall latency. However, studies have suggested that metadata caching also contribute substantially to a system as it is where all the operations are, thus reducing storage system bottlenecks. In addition, it is more cost-saving. As such, to address whether metadata caching is indeed a beneficial approach in improving storage system bottlenecks, there will be two aims for this study. The first aim is to build on the current literature and determine the contributing factors and relationships pertaining to metadata read and write I/O access during an Online Transaction Process (OLTP). Following that, the second aim of this study is to implement a filesystem with a metadata cache. To achieve both aims, three objectives were identified for each aim.